SDG's UPI 2023 thematic KKN journey in Garawangi village: Devotion, collaboration, and Memories - Anggarda, Mohammad Firos; Rizqita, Muhamad Zaidan (Universitas Pendidikan Indonesia, 2024)
The SDG's UPI 2023 Thematic KKN Program in Garawangi Village aims to provide direct benefits for students in developing skills and practical experience while positively impacting the local community. Through teaching activities in elementary schools, students' understanding of lesson concepts increases. Jamboree activities, health education, and competitions provide village communities with additional knowledge, experience, and a spirit of collaboration. With active student participation and cooperation with village heads, this program has created a mutually beneficial learning environment, positively contributing to sustainable development in Garawangi Village. This service program has succeeded in positively impacting and significantly contributing to society. By increasing community participation in activities supporting SDG achievement, students are actively involved in teaching at elementary schools, jamboree activities, health education, and organizing competitions in RW 05 Garawangi Village. Students and village communities benefit from this program, creating a mutually beneficial and synergistic learning environment between academics and village government.